El Greco's representation of mystical ecstasy - Estelle Alma Maré (Acta Theologica)
This article deals with one of El Greco’s most original inventions, namely the gesture expressing mystical ecstasy in angelic and human figures. It is introduced with a brief explanation of figural representation in Renaissance painting which was achieved by applying the premises of rhetoric in a visual way, that is by the means of the expressive gestures of figures. In El Greco’s later paintings, which were influenced by Neo-Platonic spiritual ideals, not only the figures of the angels — who are links between heaven and earth — embody spiritual ecstasy, but also human aspirants are portrayed as losing themselves in an ecstatic experience. These figures, merging themselves in a divine vision, are depicted with distinctive vertical forms, gesturing heavenwards in a specific way. The ecstatically gesturing figures are selected from El Greco’s most distinctive paintings.